Biochemical profile of domestic sewage waste water and well water irrigated vigna mungo (l.) hepper, collected from semi urban and rural areas of Coimbatore, Tamil nadu (Funded Work) - DHANYA VISWANATHAN; SIDDHURAJU PERUMAL (International Journal of Pharma and Bio Sciences, 2019)
Sewage farming is quite common in all urban areas in India. Effect of its direct and long term use for irrigation needs a thorough study. This preliminary study is an attempt to evaluate the effect of diluted sewage irrigation on cultivation of Vigna mungo (L.) Hepper from selected semi urban and rural areas of Coimbatore, Tamil Nadu. Mung bean (Vigna mungo (L.) Hepper is an important grain legume which is rich in nutrients and other bioactive compounds with many beneficial physiological effects. However, the effect of processing on properties of mung bean has not been widely studied. Impact of biologically treated domestic sewage water was studied on the growth and yield attributing characters of wheat and black gram under different fertilizer levels in the field condition. This preliminary study is an attempt to evaluate the effects of diluted sewage irrigation on cultivation of Vigna mungo (L.) Hepper from selected semi urban and rural areas of Coimbatore, Tamil Nadu. For this, parameters analyzed were: Water / Soil quality (physico-chemical parameters), Crop quality (proximate composition), and Mineral analysis (using ICP-MS) including heavy metal composition. The results demonstrated that the diluted sewage water have physicochemical properties which are below the permissible limits. Micronutrient and heavy metal contents in the plant samples were not extremely high and were within the range of FAO/ WHO standards.